The Effect of Company Reputation and Customer Experience on Customer Loyal Behavior Citylink Indonesia - *Kurhayadi Kurhayadi; Barkah Rosadi; Muhammad Yusuf; Aep Saepudin; Tuti Asmala (Riwayat: Educational Journal of History and Humanities, 2022)
The goal of this study is to see how the VIP customer research object at Citylink Indonesia Airlines affects customer loyalty. So according research on the impact of customer experience on regular customers, patrons who receive a positive are more likely to return for another purchase, more likely to recommend the business to friends, and less inclined to shift to competitors. According to the findings of this study, customer experience management factors play an important role in business competitiveness. Emotional experiences, according to the literature, play an important role in customer loyalty to a company's brand. This finding is in accordance with the study's findings that airline image and service quality have a significant influence on customer behavioral intentions. Because a brand's experience includes a consumer's subjective experience and behavior, customer experience is related to customer loyalty. The airline's image, trust, and additional services all contribute to the overall expertise. Customers whohave a happy impression and thus be willing to repurchase the service.